PICO tool for the formulation and search of clinically relevant questions in evidence-based psycho-oncology - Landa-Ramírez, Edgar; Arredondo-Pantaleón, Aranel de Jesús (Psicooncología, 2014)
The aim of this study was to provide a description of the PICO system, exemplify the use thereof for the formulation of clinically relevant questions and show how to search for papers in the field of psycho-oncology. Through this paper, the main component of PICO system and how that can be integrated to make relevant clinical questions are described. Using and example We show the way in which the psycho-oncologists can use de PICO system in their daily consultation. Finally, criticism of the tool and future research in the field are described.
Keywords: PICO system; evidence-based practice; clinically relevant questions.